“Damned if you do, doomed if you don’t”: the influence of sexism, gender, and rejection behaviors on the potential for stereotyping and workplace prejudice and discrimination - Stratmoen, Evelyn (Kansas State University, 2022)
Across three studies, the relationships between gender, rejection behavior, and ambivalent sexist attitudes on perceptions of a coworker (i.e., target) who rejects another coworker’s (i.e., suitor) romantic interest were examined. Perceptions regarding the target’s adherence to feminine gender norms, stereotyping (via the Stereotype Content Model (SCM); Fiske et al., 2002), and engagement of active harm via workplace prejudice and discrimination were examined. Factors that might influence these perceptions were manipulated, including the context of the rejection (i.e., target versus suitor), the target’s use of mitigated speech, the gender of the target, and the target’s rejection behavior. Study 1 examined the context of the rejection (i.e., being a target vs being a suitor) and gender differences in the endorsement of direct and indirect rejection strategies. Study 2 examined the effect of the target’s gender (i.e., male vs female) and their rejection behavior (i.e., direct vs indirect) on bystanders’ perceptions of the target’s adherence to feminine gender norms, stereotyping, and engaging in active harm (i.e., likelihood to engage in workplace prejudice and discrimination against the target). Study 3 examined the effect of a female target’s rejection behavior and her use of a low-powered form of communication (i.e., using mitigated speech vs not using mitigated speech) on male suitors’ perceptions of her adhering to feminine gender norms, stereotyping, and their engagement of active harm. Overall, the results showed that while men prefer direct rejection strategies (i.e., being told explicitly their romantic interest is not reciprocated), women who use these rejection strategies may be perceived as not adhering to feminine gender norms and, thereby, may experience backlash in the workplace. Furthermore, men’s hostile sexist attitudes may lead to a greater deterrent of workplace advancements and promotions for female coworkers who engage in rejection, while men’s benevolent sexist attitudes indicate expectations for women to engage in rejection behaviors that mitigate the harshness of the rejection. Therefore, women who reject a male coworker’s romantic interest may be stuck in a double bind conundrum of “damned if you do, doomed if you don’t,” where men prefer to be rejected in a straightforward manner, but there may be social consequences for doing so.
Keywords: Gender; Romantic rejection; Workplace discrimination; Stereotype content model; Ambivalent sexism